Wheat pre-anthesis development as affected by photoperiod sensitivity genes (Ppd-1) under contrasting photoperiods - Perez Gianmarco, Thomas (2018)
Fine tuning wheat phenology is of paramount importance for adaptation. A better understanding of how genetic constitution modulates the developmental responses during pre-anthesis phases would help to maintain or even increase yield potential as temperature increases due to climate change. The photoperiod-sensitive cultivar Paragon, and four near isogenic lines with different combinations of insensitivity alleles (Ppd-A1a, Ppd-B1a, Ppd-D1a or their triple stack) were evaluated under short (12 h) and long (16 h) photoperiods. Insensitivity alleles decreased time to anthesis and duration of the three pre-anthesis phases (vegetative, early reproductive and late reproductive), following the Ppd-D1a > Ppd-A1a > Ppd-B1a ranking of strength. Stacking them intensified the insensitivity, but had no additive effect over that of Ppd-D1a. The late reproductive phase was the most responsive, even exhibiting a qualitative response. Leaf plastochron was not affected but spikelet plastochron increased according to Ppd-1a ranking of strength. Earlier anthesis resulted from less leaves differentiated and a fine tuning effect of accelerated rate of leaf appearance. None of the alleles affected development exclusively during any particular pre-anthesis phase, which would be ideal for tailoring time to anthesis with specific partitioning of developmental time into particular phases. Other allelic variants should be further tested to this purpose.